A study on analytical framework to breakdown conditions among data quality measurements - Deshai, N.; Saradhi Varma, G.P; Ramana, S.V. (International Journal of Engineering and Technology, 2017)
The point of this survey is to feature issues in information quality research and to talk about potential research chance to accomplish high information quality inside an association. The survey received deliberate writing audit technique in view of research articles distributed in diaries and gathering procedures. Here built up an audit technique in light of particular subjects, for example, ebb and flow inquire about territory in information quality, basic measurements in information quality, information quality administration model and approaches and information quality evaluation strategies. In light of the audit methodology, here select pertinent research articles, concentrate and amalgamation the data to answer an examination questions. The survey features the headway of information quality research to take after its genuine application and talk about the accessible hole for future research. Research territory, for example, association’s administration, information quality effect towards the association and database related specialized answers for information quality overwhelmed the early years of information quality research. Be that as it may, since the Web is presently occurring as the new data source, the rising of new research regions, for example, information quality evaluation for web and huge information is unavoidable. This audit additionally recognizes and talks about basic information quality measurements in association, for example, information fulfillment, consistency, exactness and convenience. Likewise think about and feature holes in information quality administration model and procedures. This survey is critical to feature and break down restriction of existing information quality research identified with the current needs in information quality, for example, unstructured information sort and enormous information.